The Effect of Passive Ultrasonic Irrigation or XP-Endo Finisher on Post-Operative Pain in Patients with Necrotic Teeth with Apical Periodontitis (Randomized Controlled Clinical Trial) - Elsaka, Sherief; Hussein, Wael; Hashem, Ahmed; Soliman, Amgad (Open Access Macedonian Journal of Medical Sciences, 2022)
Objective To evaluate the effect of passive ultrasonic irrigation or XP-Endo Finisher on post-operative pain in patients with necrotic teeth with apical periodontitis using (VAS) scale at 6, 12, 24, 48, 72 hours, and 7 day time intervals. Methods Seventy-eight patients diagnosed with necrotic mandibular first molar with symptomatic apical periodontitis were randomly allocated into 1 of 3 separate groups (n=26); Navitip group (control), XP-Endo Finisher group, or Ultra X group. After a single visit root canal treatment and a specific method of agitation, depending on each group, the patients were given a questionnaire on which the patient would mark the degree of pain in a scale from 0 to 10 at 6, 12, 24, 48, 72 hours and 7 days post-obturation. Data were statistically analyzed with a significance level of P ≤ 0.05. Results Ultrasonic agitation and XP-Endo Finisher agitation as a final irrigation protocol showed significantly lower pain values than the control group, but there was no significant difference in pain values between the experimental groups. Conclusion There was significantly less pain associated with ultrasonic and XP-Endo Finisher agitation compared to Navitip irrigation.